Urgensitas Penerapan Asas-Asas Umum Pemerintahan Yang Baik Pada Konflik Rempang Eco City - Wafi, Abd.; Mas'odi, Mas'odi (Sekolah Tinggi Agama Islam (STAI) Darul Ulum Banyuanyar Pamekasan, 2024)
This study examines how the implementation of the Principles of Good Governance (AAUPB) is crucial in addressing conflicts in Rempang Eco City. The conflict significantly impacts the central government's efforts to transform Pulau Rempang and its surroundings into a hub for trade, industry, and tourism, involving various stakeholders working on the environmental project. Consequently, to resolve the conflict on Pulau Rempang, it is crucial to incorporate the principles of good governance. The goal of applying these principles is to enhance transparency and accountability in governance. They will also aid in conflict resolution and encourage active participation of the community in project decision-making. This research also analyzes the case in Pulau Rempang to illustrate the challenges and prospects of implementing good governance principles in the context of environmental conflict. The research findings indicate that applying these principles can lead to more sustainable solutions beneficial to all parties involved in the Rempang Eco City conflict. Conversely, this study helps us understand the importance of implementing good governance principles in addressing similar environmental conflicts.